Implementation of Communication Through Online-Based Applications with Schools (KABOS) at the Minahasa District Education Office - Solang, Riska Megga; Mandagi, Marthinus; Taroreh, Steven V. (Technium Social Sciences Journal, 2023)
This study aims to describe and analyze the Implementation of Communication Applications through online-based applications with schools, especially the Supervision Application Service at the Minahasa District Education Office. This research approach used a descriptive qualitative approach, with 10 predetermined informants using data collection techniques, namely observation, interviews and documentation using data analysis techniques through data reduction, data presentation and drawing verification conclusions. The results of this study indicate that I Implementation of Communication Applications through online-based applications with schools, especially supervisory application services for supervisors in basic education at the Minahasa district education office, is not optimal and good at implementing this policy as seen in the research focus which includes, (1) Application Application Communication through online-based applications with schools in supervisory application services (2) Communication Application Communication through online-based applications with schools to Supervisors. (3) Accuracy of Application Process Communication through online-based applications with schools to Supervisors then from the research results in the research focus encountered problems in the implementation process which is clearly illustrated in the Human Resources indicators and factors, where Financial and Telecommunications Equipment are not yet adequate and there is still a lack of supervisory competence in using the Application, some software is used and it is still not there are several areas that have not been reached by the internet network making it difficult for supervisors, then there is a lack of initiative and awkwardness in the Communication process between superiors and subordinates, Application Operators and Supervisors, then Supervisors and Supervisors so that the communication process does not work which affects less optimal Implementation, after that a leader is found who lack of discipline and even a lack of communication built between employees and leaders as well as supervisors and supervisors, researchers also assessed and found that not all civil servants, in this case the supervisor at the Minahasa District Education Office, correctly understood the contents and how to operate the KABOS Application, Communication (through) the Application Based Online (with) Schools so that it is very influential on the less optimal and good implementation of this Policy.